The light in the darkness: an assessment of the retributive urge - Turner, Russell Jonathan (Department of Philosophy, 2023)
In this thesis I examine in detail the retributive emotions, or the retributive urge, which typically precede retributive punishment. The four main chapters are dedicated to individual issues regarding the retributive urge: its genealogy, its schematic structure, its rationality, and its moral status. These issues draw together three philosophical fields: emotion theory, virtue ethics, and sociobiology. My conclusions are as follows. (1) Retribution and revenge are distinct forms of behaviour with different emotional bases. (2) The retributive urge has a genetic heritage, and evolved as a means to aid survival in the face of environmental pressures. (3) It consists of a complex conglomeration of components provided by its three constituent emotions: anger, fear, and disgust. (4) The common perception that the retributive urge is irrational is unjustified. (5) The manifestation of the retributive emotions suggests a virtuous character. Hence these -emotions should be encouraged within reason, rather than repressed or condemned.